Police Officers’ Attributions of Victim Culpability in Scenarios of Same-Sex Intimate Partner Violence - Goodson, Amanda (Journal of interpersonal violence, 2023)
Intimate partner violence (IPV) has garnered the attention of scholars, policymakers, and social justice actors for several decades. Shortcomings in police response to IPV may be related to police attributions of victim culpability. A dearth of research has assessed police officers’ assignment of blame, responsibility, and causality directed toward IPV victims, particularly those who identify as LGBTQ+. Using a randomly assigned, experimental vignette design, the current study employed surveys from a sample of 305 police officers commissioned at a sizeable police department in one of the most populous and diverse U.S. cities to (1) assess culpability attributions directed toward same-sex IPV (SSIPV) victims, (2) determine whether culpability attributions differed between male and female SSIPV victims, (3) examine officer demographic, occupational, attitudinal, and experimental predictors of IPV culpability attributions directed toward SSIPV victims, and (4) assess differences in predictors of culpability between male and female SSIPV victims. Results from the current study suggest police officers attributed average levels of culpability toward SSIPV victims and levels were not significantly different between male and female SSIPV victims. Adherence to heteronormative IPV myths and trauma misperceptions increased police officers’ attributions of culpability directed toward same-sex victims. Presence of physical evidence decreased culpability attributions among police officers. Educational programming developed for police officers should focus on the dynamics of IPV and cultural competency. Future research should continue to explore police officers’ perceptions of and responses to SSIPV incidents.